THE NEW PARADIGM ON THE ISLAMIZATION OF SCIENCE: ISLAM AS KNOWLEDGE AND BELIEF - Aswirna, Prima; Fahmi, Reza (Ar Raniry : International Journal of Islamic Studies, 2016)
The research based on fact about more than ten years experience the existing of Islamic Psychology Department at State Institute of Islamic Studies Imam Bonjol Padang. During the implementation of the integration on Islam and science (Psychology), The research used quantitative method as a perspective. Then I explored the problems on the capture of academic profile institution. The populations on the research were a lecturer who was teaching in the Islamic Psychology Dept. and students (about 35 people/ lecturer and 145 pupils). The sample was about 32 lecturers and 107 students. The measurement of size of respondents based on Slovin formula: N/1+N.e2. The data collected by psychological scale, observation and documentation. The regression has been used to analyze data.